Implementasi Pengelolaan Sampah Berkelanjutan: Studi Kasus Bank Sampah di Kelurahan Kotabaru, Kota Yogyakarta - Firdausi, Eyda (Jurnal Ekologi, Masyarakat dan Sains, 2024)
The city of Yogyakarta is a densely populated area that produces tons of waste every day. Waste needs to be managed to prevent negative impacts on the environment. This study aims to determine the implementation of sustainable waste management through the waste bank program. The location of this research includes 4 active waste banks in Kotabaru Village, Yogyakarta City. Data collection was carried out during September - October 2023 through observation, interview, and documentation techniques. The data obtained will be processed by data reduction, presentation, and conclusion drawing.  Waste management is an important element in efforts to create sustainable cities in accordance with SDGs 11, "Sustainable Cities and Settlements" and SDGs 12, "Sustainable Consumption and Production". According to the research results, there are 3 main factors that become obstacles to waste bank management, including public awareness, limited management resources, and weak administrative systems. The implementation of sustainable waste management through the waste bank program in Kotabaru Village has been implemented well but needs to be optimized to be effective in managing community waste.